PDE1 or PDE5 inhibition augments NO‐dependent hypoxic constriction of porcine coronary artery via elevating inosine 3′, 5′‐cyclic monophosphate level. Issue 24 (9th November 2020) - Nan, Yan; Zeng, Xueqin; Jin, Zhiyi; Li, Na; Chen, Zhengju; Chen, Jiantong; Wang, Dezhong; Wang, Yang; Lin, Zhenlang; Ying, Lei
Abstract: Hypoxic coronary vasospasm may lead to myocardial ischaemia and cardiac dysfunction. Inosine 3′, 5′‐cyclic monophosphate (cIMP) is a putative second messenger to mediate this pathological process. Nevertheless, it remains unclear as to whether levels of cIMP can be regulated in living tissue such as coronary artery and if so, what is the consequence of this regulation on hypoxia‐induced vasoconstriction. In the present study, we found that cIMP was a key determinant of hypoxia‐induced constriction but not that of the subsequent relaxation response in porcine coronary arteries. Subsequently, coronary arteries were treated with various phosphodiesterase (PDE) inhibitors to identify PDE types that are capable of regulating cIMP levels. We found that inhibition of PDE1 and PDE5 substantially elevated cIMP content in endothelium‐denuded coronary artery supplemented with exogenous purified cIMP. However, cGMP levels were far lower than their levels in intact coronary arteries and lower than cIMP levels measured in endothelium‐denuded coronary arteries supplemented with exogenous cIMP. The increased cIMP levels induced by PDE1 or PDE5 inhibition further led to augmented hypoxic constriction without apparently affecting the relaxation response. In intact coronary artery, PDE1 or PDE5 inhibition up‐regulated cIMP levels under hypoxic condition. Concomitantly, cGMP level increased to a comparable level. Nevertheless, the hypoxia‐mediated constriction was enhanced in this situation that was largely compromised by an even stronger inhibition of PDEs. Taken together, these data suggest that cIMP levels in coronary arteries are regulated by PDE1 and PDE5, whose inhibition at a certain level leads to increased cIMP content and enhanced hypoxic constriction.